2023
DOI: 10.1371/journal.pone.0288558
|View full text |Cite
|
Sign up to set email alerts
|

Use of very short answer questions compared to multiple choice questions in undergraduate medical students: An external validation study

Abstract: Multiple choice questions (MCQs) offer high reliability and easy machine-marking, but allow for cueing and stimulate recognition-based learning. Very short answer questions (VSAQs), which are open-ended questions requiring a very short answer, may circumvent these limitations. Although VSAQ use in medical assessment increases, almost all research on reliability and validity of VSAQs in medical education has been performed by a single research group with extensive experience in the development of VSAQs. Therefo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…One possible reason for this is that the final exam contained SAQs in addition to MCQs, whereas the mid-semester exam was solely MCQs. A recent study has shown that medical students perform better in MCQs than SAQs in examinations (van Wijk et al, 2023). As a follow-on, the difference between the marks for the exams and wet laboratories in the present study could have been even greater if SAQs had been included in the mid-semester exam.…”
Section: Modelling Changing the Proportional Allocation Of Marks Betw...supporting
confidence: 51%
“…One possible reason for this is that the final exam contained SAQs in addition to MCQs, whereas the mid-semester exam was solely MCQs. A recent study has shown that medical students perform better in MCQs than SAQs in examinations (van Wijk et al, 2023). As a follow-on, the difference between the marks for the exams and wet laboratories in the present study could have been even greater if SAQs had been included in the mid-semester exam.…”
Section: Modelling Changing the Proportional Allocation Of Marks Betw...supporting
confidence: 51%
“…From preprint to published article, 7 articles (7.3%) adjusted author order, but retained the same authorship team. Of these articles, only one changed the first author 35 and in two cases the last author was shifted to a new author order location. 36,37 Thirteen preprints (13.5%) had authors added (n=10) or removed (n=3) when they later appeared in a peer-reviewed journal.…”
Section: Authorshipmentioning
confidence: 99%